المعايير التخطيطية لأنقسام الوحدات السكنية في بلديتي الغدير والكرخ - Al-Ajili, Muhammad Saleh Rabeeh; Jassim, Qadisiyah Hussein (Al-Adab Journal, 2021)
The research was based on knowing the most important planning criteria for the division of housing units in the municipalities of Al-Ghadeer and Al-Karkh, how to adhere to their application, and the main reasons that led to the division. Among the most important of these criteria are standards related to the family and standards related to the housing unit, and it was found through the application of these standards on the housing units in the search area that most of them were not applied by the residents therein, and that all social reasons represented an increase in the number of family members, and the number of families that Caused by housing overcrowding within the housing unit, and economic reasons such as a decrease in the level of income and administrative reasons such as failure to develop a current or future plan to address the housing crisis, or for a personal reason such as renting a housing unit for the purpose of renting or selling it or for another reason, all of these factors contributed effectively to the spread The phenomenon of dividing residential units into more than one section and not adhering to the planning standards agreed upon by the Ministry of Planning, which generally affected all infrastructure or superstructure services in the research area.